Memupuk Sinergi: Pengembangan Pariwisata Dewi Belai Melalui Pendekatan Model Pentahelix - Ihsan, Muhammad Afdhal; Zulfiani, Dini (Jurnal Paradigma, 2025)
The study aimed to identify and describe the collaborative development of Dewi Belai in Batuah Village, examining both the facilitating and hindering factors in this process. Employing a qualitative descriptive methodology, the research investigated variables influencing the cooperative growth of tourism attractions on the Benua Elai. Key informants included the Village Head of Batuah, PT. Baramulti Suksessarana, Samarinda State Polytechnic, Kutai Kartanegara Regency Communication, and Information Service, and a journalist from Kaltimkece. id. Kelompok Tani Borneo Hijau also contributed valuable information. Data collection involved observation, interviews, and documentation. Miles, Huberman, and Saldana's interactive model guided the data analysis. The qualitative analysis revealed that the collaborative development of Dewi Belai using the Pentahelix Model in Batuah Village faced challenges due to insufficient focus on infrastructure development and a lack of public trust. Despite having the necessary resources and willingness from involved parties, the management of tourism sites faced obstacles such as poor cooperation and limited communication between the village authority and the local population. This hindered the success of the collaborative development initiative in promoting tourism spots on the Dewi Belai.